Phenomenological research on the motivation and self-directedness of recreational motocross athletes returning to the sport after significant injury - Young, Daryn (My University, 2025)
Participation in recreational extreme sports is on the rise, but with extreme sport participation comes significant injuries. Recreational extreme athletes endure a variety of significant injuries that hinder their normal function and sometimes cause permanent, life-altering trauma. Due to the individualistic and recreational nature of these extreme sports, the athletes involved do not participate for monetary reasons, career aspirations, or the pursuit of fame. It is unclear what motivation and self-directedness these athletes experience when returning to their recreational extreme sport after sustaining a significant injury. This study used a hermeneutic phenomenological framework to analyze the motivation and self-directedness of recreational motocross athletes who continue their participation after sustaining a significant injury in recreational motocross. Self-determination theory and self-directed learning theory guided the research. To maintain consistency in participant selection and phenomenon experienced, a part of the selection criteria is participation in recreational motocross. Participants had sustained a significant injury through their participation in the sport, and continued their participation once rehabilitated. Data were collected through two semi-structured interviews. This study included six participants. Data from interviews, researcher journaling, and analytic memos were analyzed for emerging patterns and themes using the hermeneutic phenomenological framework. Key findings of motivation and characteristics of self-directedness were found. Several themes emerged and included getting the most out of life, social forces to quit from outside the sport, friendship and camaraderie, feelings of accomplishment, special intrinsic sensation, desire to have fun, responsibility for injury and rehabilitation, sought information, fearful of reinjury, why do I want to keep doing this, and changing their strategies within the sport.
Keywords: Injury rehabilitation; Extreme athletes; Self-determination theory; Self-directed learning